Analisis Lem Kuku Cair dan Gel Dilihat dari Bentuk dan Ukurannya - Esta Ramadhani Windyastari; Ifa Nurhayati; Anik Maghfiroh (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study was conducted to analyze the results of the differences between liquid nail glue and gel nail glue based on the effectiveness of their use. The method used was direct observation by conducting experiments on several commercial products, accompanied by simple testing on the ease of application, adhesion, and durability of the results of use in four female participants. The results showed that although liquid nail glue has a smaller packaging and a thinner texture making it easy to apply, its adhesion tends to be lower and less durable. In contrast, gel nail glue that is generally packaged in larger containers with a thicker consistency has been shown to provide stronger adhesion as well as higher resistance to the nails. This study aims to analyze the difference between liquid nail glue and gel nail glue in its application to gel press-on nails, by reviewing the packaging shape, product size, and adhesion effectiveness. This research is simple experimental/comparative. Observations were made through direct application tests using several types of press-on nails. The results show that liquid glue, although easy to apply, tends to be less stable on the surface of the press-on gel and comes off more quickly. In contrast, gel nail glue with its thick texture provides stronger adhesion and is able to maintain press-on nails longer, even at intensive daily activities. Therefore, gel glue is considered much more effective and is recommended as the main choice for gel press-on nail installation.